Requirements for the Application of Governance Standards in Faculties of Education in Arab Universities - Hussen, Bannaga (Emerging Trends in Education, 2023)
This study aimed to identify the requirements for applying the dimensions of governance in the faculties of education in Arab universities. The descriptive analytical method was used, analyzing the content of previous studies related to the topic. The most important results are that the faculties of education in Arab universities actually apply, to a moderate degree, the dimensions of governance in their management, as well as for some instances of self-monitoring, development and sustainability. It also came out with a number of recommendations, the most important of which are: issuing regulations and legislation related to governance standards in the faculties of education in Arab universities, establishing independent committees within the faculties of education to follow up and evaluate the implementation of governance standards, adopting unified and declared standards for the various faculties of education in Arab universities, strengthening the role of the Union of Arab Universities, and consolidating the bonds of partnership between the union and the faculties of education. Keywords: Implementation of governance; Governance Standards; Faculties of Education; Arab universities; Descriptive Analythical Method.